2015
DOI: 10.1016/j.sbspro.2015.06.167
|View full text |Cite
|
Sign up to set email alerts
|

Makerspaces and Contributions to Entrepreneurship

Abstract: Entrepreneurship is essential to the growth and dynamism of countries and regions, forcing policy makers to search for levers to generate new firms within their municipalities. Without public attention, the maker movement, which refers to the democratization of access to and information on using tools, has risen from a fringe hobby to a prominent lifestyle with important implications for public concern. Modernly, tools have been available only to those working within firms and industry or those willing to pay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(40 citation statements)
references
References 23 publications
0
32
0
8
Order By: Relevance
“…Espaços desta natureza são, em última instância, sistemas experimentais e justamente por isso um sistema experimental não traz as respostas e perguntas convencionais [11] . A variedade de finalidades dos espaços maker é fluida, como menciona Holm [12] cada espaço maker é único e a maneira como ele contribui com a comunidade local é determinada pelos fundadores e membros. Alguns makerspaces têm um foco mais empreendedor e oferecem serviços similares a incubadoras ou espaços coworking com o benefício adicional dos equipamentos internos.…”
Section: Espaço Maker: Compreendendo O Conceito De Espaços Maker Sua Gênese E Desenvolvimento No Mundo E No Brasilunclassified
See 1 more Smart Citation
“…Espaços desta natureza são, em última instância, sistemas experimentais e justamente por isso um sistema experimental não traz as respostas e perguntas convencionais [11] . A variedade de finalidades dos espaços maker é fluida, como menciona Holm [12] cada espaço maker é único e a maneira como ele contribui com a comunidade local é determinada pelos fundadores e membros. Alguns makerspaces têm um foco mais empreendedor e oferecem serviços similares a incubadoras ou espaços coworking com o benefício adicional dos equipamentos internos.…”
Section: Espaço Maker: Compreendendo O Conceito De Espaços Maker Sua Gênese E Desenvolvimento No Mundo E No Brasilunclassified
“…Pensando na inter-relação entre a cultura maker e empreendedorismo, Holm [12] salienta que ela pode se dar, principalmente, por três aspectos. O primeiro é que a cultura maker incentiva o design de produtos e assim pode "lançar" mais "empreendedores acidentais".…”
Section: Entrevistado 3: Sim O Contato Com O Lite Me Fez Despertar Uma Paixão Por Desenvolvimento De Novos Produtos E Me Incentivou a Comunclassified
“…This exchange also maximizes the use value of intellectual property, which is an essential element of an open business plan. In the work, the model created was inspired by multisided platforms and open source [87], where the first step is to analyze the whole project before a sequence of questions based on the Canvas model [88]. The tool consists of nine inter-related building blocks around four critical components: "value proposition, value creation, value capture and value delivery" [89][90][91].…”
Section: Business Models and Additive Manufacturingmentioning
confidence: 99%
“…Recent studies have discussed the role of these spaces in local economic development processes (Van Holm, 2017), and their relationship with entrepreneurs (Gertner & Mack, 2017). Research has also confirmed the impact of CWSs on education and employment creation (van Holm, 2015;Wang & Loo, 2017;Wolf-Powers et al, 2017), as well as the importance of entrepreneurial co-location within cities more generally (Andersson & Larsson, 2016;Witt, 2004). However, there is still a need in the current policy framework to specifically address the implications of these developments on economic and spatial planning.…”
Section: How Do We Understand Co-working Spaces?mentioning
confidence: 99%